Evaluation of Inflammatory Biomarkers in the Diagnosis of Type 2 Diabetes Mellitus Complications - Raghad Hasan Nafal; Mohammed Hayder Asker (American Journal of Bioscience and Clinical Integrity, 2026)
Type 2 diabetes mellitus (T2DM) is also becoming known as a chronic metabolic and inflammatory disease and where low-grade inflammation is persistent, it is a primary cause of insulin resistance, endothelial malfunction, and tissue damage. An expanding numbers of inflammatory biomarkers such as hs-CRP, IL-6, TNF-a, and hematological indicators like NLR, PLR, and SII give valuable information about the presence inflammatory conditions in the patients with T2DM. These biomarkers have demonstrated close correlation with the manifestation and progression of the significant diabetic complications, especially the nephropathy, retinopathy, neuropathy, and cardiovascular disease. They are clinically useful in the sense that they can assist in the process of early detection, improve the process of risk stratification and complement the conventional metabolic indicators like fasting glucose and HbA1c. Nevertheless, inflammatory biomarkers do not live up to the promise because they have low specificity, variability by non-diabetic disease, and no universally accepted reference cutoffs. Hence, although they are not to be used as substitute diagnostic means, the use of these biomarkers in a standard clinical examination can enhance the early detection of individuals at a high risk and help to prevent and treat the long-term complications of T2DM.